LATENTIATED PRODRUG APPROACH OF DRUGS: AN OVERVIEW - P. R., DHARUN; Y., ISMAIL; PRASAD M., VIJAYA VARA (International Journal of Applied Pharmaceutics, 2021)
Prodrugs, with their capability of declining the adverse events and elevating the bioavailability of certain drugs, have captured enormous attention throughout the world since the 20th century. The versatility of the prodrugs that are inert and after administration releasing the parent moiety for the desired effect has become a major criterion for the scientists to incorporate this to alleviate the undesired effects of a conventional drug. About 10% of the prevailing drugs are prodrugs and their usage is being amplified owing to its critical application in cancer therapy, toxicity alleviation, and specificity. The purpose of this review is to understand the prodrugs, strategies incorporated in designing the prodrugs, applications, their crucial benefits in targeted action at a specific site of the body, their advantageous effects in chemotherapy. Also, to be acknowledged with the ongoing clinical trials and researches on prodrugs and some notable marketed prodrugs in a depth manner.